Cross-Cultural Care: The Experiences of Pediatric Nurses in Providing Culturally Sensitive Care to Children and Their Families - Abdulaziz M. Alodhailah; Majed M. Aljabri; Abdullah Alharbi; Bader M. Almutairy; Faihan F. Alshaibany; Mohammed Almutairi (Healthcare, 2026)
Background: Saudi Arabia’s healthcare system serves an increasingly diverse patient population, yet limited qualitative evidence exists regarding how pediatric nurses navigate cultural complexity in their daily practice. Understanding nurses’ day-to-day experiences of cross-cultural care is essential for strengthening culturally sensitive pediatric services. Purpose: This study explored the experiences of pediatric nurses in providing culturally sensitive care to children and their families in Riyadh, Saudi Arabia. Methods: A qualitative descriptive study was conducted in pediatric units of tertiary hospitals in Riyadh City, Saudi Arabia. Eighteen pediatric nurses participated in semi-structured interviews. Data were analyzed using Braun and Clarke’s reflexive thematic analysis, and reporting followed the Consolidated Criteria for Reporting Qualitative Research (COREQ) guidelines. Results: Four themes emerged: navigating cultural landscapes, describing nurses’ encounters with diverse cultural beliefs and health practices; communication as a bridge and a barrier, reflecting language challenges and strategies for meaningful engagement; balancing professional standards with cultural respect, highlighting the tension between evidence-based care and cultural accommodation; and the emotional labor of cross-cultural caregiving, capturing the personal toll and resilience involved in culturally diverse practice. Conclusions: Pediatric nurses engage in complex interpretive, relational, and emotional work when providing culturally sensitive care. Institutional support through cultural competence training, multilingual resources, and organizational policies is essential for enhancing culturally responsive pediatric nursing practice in diverse healthcare settings.